Türk hukuku'nda grev yasakları ve ILO normları - (:unkn) unknown (My University, 2014)
Grev hakkı anayasal bir hak olmasına karşın, sınırsız bir hak değildir. Grev hak olarak getirilip güvence altına alınırken bir taraftan da birtakım yasaklamalara ve sınırlamalara tabi tutulmuştur. Grevin yasaklanmasına ve ertelenmesine ilişkin olarak Anayasada düzenlenen esaslar çerçevesinde 6356 sayılı Sendikalar ve Toplu İş Sözleşmesi Kanununda birtakım düzenlemeler getirilmiştir. Türk çalışma hukukunu ILO sözleşmeler i ile uyumlu hale getirmeyi ve uygulamada karşılaşılan çeşitli sorunları çözmeyi amaçlayan bu yeni kanun bazı olumlu düzenlemeler içermesine rağmen ulusal ve uluslararası forumlarda yönetilecek eleştirilerin devam etme ihtimali vardır. Bu kapsamda, yapılan çalışmada grev yasakları ve ILO normları değerlendirilmiştir.

The right to strike is a constitutional right. Although strike is a constitutional right, it is not a limitless right at all. While it is deemed to be a right and thus secured, it is subject to several restrictions and limitations. The Labor Unions and Collective Agreements Act. numbered 6356 was regulated within the framework of the procedural basis in the Constitution regarding the prohibition and suspension of the strike. Aiming to bring the labor relations law of Turkey into conformity with ILO norms on freedom of association as well as to find solutions to practical problems of implementation, the Act numbered 6356 carries various positive provisions. Despite the introduction of various positive elements, the new Act is likely to continue being challenged in national and international forums. Within this framework, strike bans and ILO norms will be assessed in this study.
Strike bans in the Turkish law and ILO norms
Keywords: Hukuk